Cloning and molecular characterization of DNA Fragments Obtained From 3' - Race Of Starch Branching Enzyme From M. Sagu - Tan,, Whei Shien. (Universiti Malaysia Sarawak (UNIMAS), 2009)
The complete genome sequence of starch branching enzyme (SBE) in Metroxylon sagu is not yet established. The main aim of this study is to amplify the flanking 3'-region of partial coding sequence of SBE I in M. sagu using 3'-RACE PCR. RACE PCR utilizes gene specific primer (GSP) and oligo(dT) primer.. The RNA from M. sagu leaf was extracted and reverse-transcribed into cDNA using M-MuLV reverse transcriptase. The second strand was then amplified using 3'-RACE PCR method. PCR product was purified using Vivantis GF-l PCR Clean-up kit. Cloning of PCR product was carried out using E. coli XL 1 Blue and pGEM-T Easy Vector Systems. The plasmid was extracted using miniprep isolation method and Vivantis GF-l Plasmid Extraction kit and digested by EcoRl. Colony PCR was performed for indication of inserted gene. In this study, the transfonnation and cloning of PCR product failed as the transformants were contaminated with Bacillus and the sequence blasted showed the presence ofxylanase instead ofSBE.